DEVELOPMENT AND CREATION OF THE «CLASSIFICATION OF DEFECTS OF HOT ROLLED SEAMLESS PIPE PRODUCTION OF JSC «BMZ – MANAGEMENT COMPANY OF HOLDING «BMK» - I. A. Kovaleva; N. A. Hodosovka; I. A. Guzova; N. A. Glazunova; O. V. Rozhkov (Литьë и металлургия)
With the development of a new process for the production of seamless hot-rolled pipes, specialists of the enterprise encountered difficulties in determining the causes of unsatisfactory quality of pipes, determining their nature and causes. In this regard, this article contains created and developed «Classification of defects of hot rolled seamless pipes made of OJSC «BSW – management company of «BMC» holding».